The western Pacific subtropical high and tropical cyclone landfall: Seasonal forecasts using the Met Office GloSea5 system - Camp,J; Roberts,MJ; Comer,RE; Wu,P; MacLachlan,C; Bett,PE; Golding,N; Toumi,R; Chan,JCL (Quarterly Journal of the Royal Meteorological Society, 2019)
We investigate the relationship between the western Pacific subtropical high (WPSH) and tropical cyclone (TC) landfall in the ERAInterim reanalysis and two configurations of the UK Met Office Global Seasonal forecasting system version 5 (GloSea5): Global Atmosphere 3.0 (GA3) and Global Coupled configuration 2 (GC2). Both model configurations have the same horizontal and vertical resolution in the ocean and the atmosphere, but differ in terms of model physics. The WPSH strongly modulates TC activity over the subtropical western North Pacific (WNP) and TC landfall over East Asia (Japan, Korea and East China). Here we show that both model configurations GA3 and GC2 show significant skill for predictions of the WPSH and TC variability over the subtropical WNP, as well as TC frequency along the coast of East Asia, during the boreal summer (June–August). An extension of the analysis to include the full WNP typhoon season (June–November) is also examined; however, only a weak significant relationship between the WPSH index and the observed TC frequency over East Asia is found during this period, and no significant relationship is present in either GloSea5 GA3 or GC2. Results highlight the potential for operational seasonal forecasts of TC landfall risk for Japan, Korea and East China over the June–August period using predictions of the WPSH indices from GloSea5.